Anogenital diseases associated with HPV infection - V N Prilepskaya; N M Nazarova; L A Sulamanidze; O V Burmenskaya; D Yu Trofimov; S V Pavlovich (IP Berlin A.V., 2015)
The review examined the role of HPV in anogenital diseases. There are presented modern data on the prevalence of anal intraepithelial neoplasia (AIN), HPV infection of the anal region among women at risk (cervical intraepithelial neoplasia - CIN, vulvar - VIN, vaginal - VaIN). There are considered methods of diagnosis of HPV-associated anogenital diseases. Analyzes the literature on the importance of the development of screening AIN in patientswith CIN, VIN, VaIN. There are presented data of the preliminary results of the research of HPV infection of the anal region in patients with genital neo-plasias, the data on different tropism of HPV to cervical epithelium and the epithelium of the anal region.